Finding your element : How to discover your talents and passions and transform your life - Robinson, Ken, 1950-2020; Aronica, Lou (New York : Viking, 2013)
In this companion to the international bestseller The Element, Sir Ken Robinson returns to the subject of his celebrated TED talks, offering a practical guide to discovering your passions and natural aptitudes, and finding the point at which the two meet: your element.
Includes bibliographical references (pages 245-251) and index.
Keywords: Self-actualization (Psychology); Self-realization